Arts Therapies for Anxiety, Depression, and Quality of Life in Breast Cancer Patients: A Systematic Review and Meta-Analysis. (22nd April 2014) - Boehm, Katja; Cramer, Holger; Staroszynski, Thomas; Ostermann, Thomas
Abstract : Background . Breast cancer is one of the most common types of cancer. However, only a few trials assess the effects of arts therapies. Material and Methods . We searched the Cochrane Central Register of Controlled Trials, PubMed, and Google Scholar from their start date to January 2012. We handsearched reference lists and contacted experts. All randomized controlled trials, quasi-randomized trials, and controlled clinical trials of art interventions in breast cancer patients were included. Data were extracted and risk of bias was assessed. Meta-analyses were performed using standardized mean differences. Results . Thirteen trials with a total of 606 patients were included. Arts therapies comprised music therapy interventions, various types of art therapy, and dance/movement therapies. The methodological quality ranged from poor to high quality with the majority scoring 3 of 4 points on the Jadad scale. Results suggest that arts therapies seem to positively affect patients' anxiety (standardized mean difference: −1.10; 95%, confidence interval: −1.40 to −0.80) but not depression or quality of life. No conclusion could be drawn regarding the effects of arts therapy on pain, functional assessment, coping, and mood states. Discussion . Our review indicates that arts interventions may have beneficial effects on anxiety in patients with breast cancer.